Monitoring the degradation of nuclear waste packages induced by interior metallic corrosion using synchrotron X-ray tomography. (10th August 2019) - Paraskevoulakos, C.; Stitt, C.A.; Hallam, K.R.; Banos, A.; Leal Olloqui, M.; Jones, C.P.; Griffiths, G.; Adamska, A.M.; Jowsey, J.; Scott, T.B.
Graphical abstract: Highlights: Synchrotron X-ray tomographic scans on miniaturised ILW drum – simulant packages. Grout failure to accommodate internal uranium corrosion – induced volume expansion. Steel encasement did not exhibit signs of distortion. Two fold role of the uranium oxide on the behaviour of the waste packages. Abstract: Within the British nuclear inventory, waste is classified into three main categories, including Intermediate Level Waste (ILW). ILW mainly consists of fuel casing metallic swarf, where parts of uranium metal are also expected to have been agglomerated. ILW treatment route includes the material storage in stainless steel drums and subsequent grout encapsulation. The solidified matrix is believed to maintain the radioactive waste fully confined and immobile. Recent inspections revealed mechanical distortion around the steel liner in a proportion of the inspected drums. The distortion has been ascribed to the corrosion of the encapsulated metallic parts. The generated corrosion products occupy greater volume than the parent metal, resulting in an internal volume expansion which imposes stress/strain on the encapsulants. This study attempts to correlate the level of internal corrosion with the magnitude of package degradation in ILW drum–simulant systems by favouring the use of powerful synchrotron X-rays.